2005
DOI: 10.1007/s11222-005-3393-z
|View full text |Cite
|
Sign up to set email alerts
|

Accurate ARL computation for EWMA-S2 control charts

Abstract: Originally, the exponentially weighted moving average (EWMA) control chart was developed for detecting changes in the process mean. The average run length (ARL) became the most popular performance measure for schemes with this objective. When monitoring the mean of independent and normally distributed observations the ARL can be determined with high precision. Nowadays, EWMA control charts are also used for monitoring the variance. Charts based on the sample variance S 2 are an appropriate choice. The usage of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
34
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 33 publications
2
34
0
Order By: Relevance
“…The same could be observed in papers about ARL computation for single variance control charts (see Knoth, 2005 for more details). In Knoth and Schmid (2002) the combined X-S 2 EWMA scheme was analyzed, but with less accuracy than Gan (1995) provided.…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…The same could be observed in papers about ARL computation for single variance control charts (see Knoth, 2005 for more details). In Knoth and Schmid (2002) the combined X-S 2 EWMA scheme was analyzed, but with less accuracy than Gan (1995) provided.…”
Section: Introductionsupporting
confidence: 74%
“…The reason behind the lack of precision is that the methods usually applied for ARL calculation are not able to handle the restricted support of the chart statistic (S 2 and, of course, S and the range R are nonnegative random variables). While in Knoth (2005) this problem is treated for single variance monitoring by solving integral equations with collocation methods, this paper employs collocation and ideas similar to Gan (1995) in order to obtain accurate ARL values of X-S 2 EWMA control charts. Additionally, the appropriate choice of the nonsymmetric control limits for the S 2 part of the scheme is addressed.…”
mentioning
confidence: 99%
“…Knoth (2005) demonstrated that the collocation method is fast and accurate in calculating the ARL of an exponentially weighted moving average control chart for monitoring the variance of normally distributed data. Consider a CUSUM chart obtained by plotting C n = max(0, C n−1 + W n ), against the sample number n where C 0 = u, 0 ≤ u < h and W n is the log-likelihood ratio statistic…”
Section: Appendix D: Cdf and Pdf Of W(y S)mentioning
confidence: 99%
“…To solve for c j 's, we choose a set of N nodes in the domain [0, h], and then solve the resulting system of linear equations as discussed in Hackbusch (1995). According to Knoth (2005), the Chebyshev polynomials T j (z) = cos((j − 1) arccos(z)), z ∈ [−1, 1], j = 1, . .…”
Section: Appendix D: Cdf and Pdf Of W(y S)mentioning
confidence: 99%
“…[30] compared the performances of the Markov chain approach and the simulation method to approximate ARL and showed that there was no significant difference between them. Knoth [14] did a comparison between Markov chain and integral equation approaches in terms of ARL evaluation of EWMA-S 2 control charts. Rigdon [29] applied the integral equation method for the calculation of in-control ARL (ARL 0 ) and out-of-control ARL (ARL 1 ) for the MEWMA charts.…”
Section: Introductionmentioning
confidence: 99%